THE ROLE OF ISLAMIC RELIGIOUS EDUCATION IN THE FORMATION OF MUSLIM PERSONALITY IN MTSS AT TAQWA SETU STUDENTS - Ropiah, Siti; Lasmini, Dewi (Universitas Islam Madura, 2025)
The purpose of this article is to analyze the role of Islamic Religious Education in the formation of Muslim personality among MTsS At-Taqwa Setu students. Islamic religious education has a strategic role in shaping attitudes, behaviors, and religious understandings that are in accordance with Islamic values. The main focus of this research is how PAI can be an effective medium to build the character of students who have faith, piety, and noble character. In this study, a qualitative approach was used with a case study method, involving observation, interviews with PAI teachers, and documentation of learning activities at MTsS At-Taqwa Setu. The results of the study show that PAI plays an important role in shaping students' personalities through the teaching of noble moral values, teacher examples, and extracurricular religious activities. Effective implementation of PAI is able to encourage students to develop resilient and adaptive Muslim personalities in daily life. This study suggests the improvement of innovative and experience-based teaching methods, as well as collaboration between schools, families, and the community in supporting the formation of students' character. The implication of this research is that this research can enrich the study of Islamic religious education as the main factor in the formation of the character and personality of Muslim students. Adding references for academics and education practitioners in understanding the relationship between Islamic religious education and the formation of student morals and ethics. The results of the research can be used by schools to improve the teaching methods of Islamic religious education to be more effective in forming a strong Muslim personality.